Immunodominance of HLA-A2-restricted Hepatitis C virus-specific CD8+ T cell responses is linked to naïve-precursor frequency - Schmidt, Julia; Neumann-Haefelin, Christoph; Altay, Tayibe; Gostick, Emma; Price, David A.; Lohmann, Volker; Blum, Hubert E.; Thimme, Robert (Journal of virology, 2011)
The impact of naïve-precursor frequency on human virus-specific CD8+ T cell immunodominance is not well understood. Using a recently developed major histocompatibility complex (MHC) class I tetramer enrichment protocol, we found a conserved hierarchy and a >10-fold difference in naïve-precursor frequencies across three HLA-A2-restricted hepatitis C virus (HCV)-specific epitopes. Importantly, the NS31406 epitope with the highest naïve-precursor frequency in healthy donors was also the most frequently targeted epitope in a large cohort of chronically HCV-infected patients, both ex vivo and after in vitro stimulation. These results indicate for the first time that immunodominance in a human viral infection is linked to naïve-precursor frequency.
Gesehen am 12.10.2022
Im Titel ist das Pluszeichen hochgestellt